Exploring the time to intervene with a reactive mass vaccination campaign in measles epidemics - GRAIS, R. F. (Cambridge University Press, 2006)
The current WHO policy during measles outbreaks focuses on case management rather than reactive vaccination campaigns in urban areas of resource-poor countries having low vaccine coverage. Vaccination campaigns may be costly, or not timely enough to impact significantly on morbidity and mortality. We explored the time available for intervention during two recent epidemics. Our analysis suggests that the spread of measles in African urban settings may not be as fast as expected. Examining measles epidemic spread in Kinshasa (DRC), and Niamey (Niger) reveals a progression of smaller epidemics. Intervening with a mass campaign or in areas where cases have not yet been reported could slow the epidemic spread. The results of this preliminary analysis illustrate the importance of revisiting outbreak response plans.